Application of Criminal Sanctions against Theft Perpetrators in Forced Conditions (Comparison of Positive Law and Islamic Law) - Yoga Rizka Kusuma; Bambang Sukoco (Universitas Muhammadiyah Surakarta, 2023)
Crimes against the property or wealth of others have occurred in many communities. This is done in various ways and opportunities are done alone or also done in groups. The law of theft is divided into several kinds of criteria depending on how much loss from the goods taken. Judging from the positive law, the crime of theft has been regulated in articles 362-367 of the Criminal Code which in these articles have criteria and additional weights in order to provide justice for potential victims and potential defendants. Whereas when viewed from the review of Islamic law, the rule will remain at any time because it has been explained in the Qur'an and hadith and the punishment limit for the severe, and the punishment of tak'zir for the light. The results of this study will show, among others, the similarities and differences in the application of criminal sanctions in terms of positive law and Islamic law. Both have similarities that both have criteria in the sanctions given to provide a deterrent effect, while the difference between the two from the law used is because Islamic law uses the legal basis of the Qur'an, hadith, and the agreement of scholars.